Empathy and emotional intelligence as protective factors of mental health in students of the National University of Itapúa in times of Covid-19 (Journal on studies and research of academic knowledge, 2022)
Empathy and emotional intelligence are associated with the protective and empowering mechanism of mental health. The aim of this study was to evaluate the components of empathy and emotional intelligence as protective factors of mental health in students of the National University of Itapúa, Paraguay, during COVID-19. It is a quantitative design, descriptive type of probabilistic sampling, in which we worked with a sample of 252 students of Humanities and Medicine in the application of the IRI and TMMS-24. The results obtained, with respect to empathic components according to gender and faculties, show a notable difference in terms of distress. Regarding the emotional dimensions, 59% of the students have an adequate level of emotional well-being. And the factors that contribute to their mental health are self-esteem, positive attitude, physical activity, good habits, emotional support, empathy, self-control, recreation. From the salutogenesis approach, the study shows that students have developed strategies of empathy and emotional intelligence as intrinsic values in response to covid-19 and that they act as protective factors for their mental health.
Keywords: Empathy; Emotional intelligence; Mental health; Students; COVID-19